Early Childhood Education : In The Past, Present and Future - Syafrida, Rina; Maryati, Mimin; Permana, Hinggil (JECCE (Journal of Early Childhood Care and Education), 2019)
This study aims to analyze the early childhood education development in the past in terms of the establishment history of an institution, the early childhood education development and implementation today and the early childhood education development in the future is seen based on the needs analysis and expectations of parents and educator. The study was conducted for 3 months from February to April 2019 at the Global Islamic School institution, on Jalan Raya Condet, East Jakarta. The research method is a qualitative approach with a case study strategy that aims to research natural object conditions, researchers act as key instruments, triangulation data collection techniques, inductive data analysis and qualitative research results emphasize more on meaning than generalization. The conclusion obtained is that the Global Islamic School combines two main concepts, namely the formation of the character of a Muslim with a global insight and combines the 4 concepts of the nature of the child, namely the heart, mind, exercise and feeling in helping children develop their potential and abilities.